A Method for Verifying the Applicability of Tramway Projects. (July 2023) - Chatziparaskeva, Martha; Pyrgidis, Christos; Kepaptsoglou, Konstantinos
Feasibility studies of transportation projects often require significant technical input, which should normally be the outcome of sub-sequent studies. An early assessment and screening of technically suitable project alternatives in the form of applicability verification could yield significant cost and time savings for planners, decision makers and stakeholders. The objective of this paper is to develop a comprehensive approach for the technical applicability verification of tramway systems. The proposed method considers different applicability aspects in a systematic manner and allows for quickly assessing whether a project may be implemented, in the context of a preparatory process. A case study of the applicability verification method for the case of a planned tram line in Thessaloniki, Greece, demonstrates the potential of the proposed method.